Pengembangan Perangkat Pembelajaran Berbasis Saintifik untuk Siswa Sekolah Dasar - Astutik, Fitriyah Ika (Mitra PGMI: Jurnal Kependidikan MI, 2024)
This research is development research which aims to develop scientific-based learning tools for elementary school students in science subjects that are valid, practical, and effective. The learning tools developed include Learning Objectives Flow (ATP), Teaching Modules, Student Worksheets (LKPD), Student Assessment Sheets, Learning Activity Observation Sheets and Student Textbooks. This research refers to Plomp & Nieveen which is connected to the stages according to Thiagarajan using the 4-D model including 4 stages, namely the stage Define, Design, Development, and Disseminate. The device developed was tested on 23 grade IV elementary school students. The results obtained in this research state that the learning tools that have been developed meet the categories of valid, practical, and effective.